Peran Guru Dalam Meningkatkan Motivasi Belajar Siswa Pada Mata Pelajaran Qur’an Hadis di Madrasah Ibtidaiyah - Suhardi, Suhardi; Sutrisno, Sutrisno; Maisalamah, Maisalamah (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2023)
Learning motivation is one of the main factors that determine the success of the learning process, especially in the Qur'an Hadith subject in Madrasah Ibtidaiyah. However, low student learning motivation is often an obstacle in achieving optimal learning objectives. This study aims to examine the role of teachers in improving student learning motivation in the Qur'an Hadith subject in Madrasah Ibtidaiyah through a literature study approach. This study uses a descriptive qualitative method with a library research approach, where data is collected from various primary literature sources such as scientific journals, research articles, and secondary sources such as reference books and educational documents. The results of the study indicate that teachers have a very important role in improving student learning motivation, namely as motivators, facilitators, and guides in the learning process. The strategies used by teachers include giving praise and rewards, using a variety of learning methods, and creating a conducive and enjoyable learning atmosphere. In addition, parental involvement, availability of facilities, and a supportive school environment are also important factors in increasing student motivation. The implication of this study is the need to improve teacher pedagogical competence, especially in classroom management and innovation of learning methods that are in accordance with the characteristics of elementary school students. This study is expected to be a reference for teachers, madrasah principals, and Islamic education policy makers in designing learning strategies that can improve student motivation and learning outcomes as a whole.